Febuxostat Protects Human Aortic Valve Endothelial Cells From Oxidized Low-density Lipoprotein–Induced Injury and Monocyte Attachment. Issue 6 (December 2022) - Liang, Xiangwen; Li, Ping; Xie, Wenchao; Lin, Zhihai; Wang, Zhengdong; Zeng, Shuyi; Liu, Ming
Abstract: Atherosclerosis (AS) is a common cardiovascular disease with high morbidity and mortality. The pathogenesis of AS is closely related to endothelial dysfunction, which is mainly induced by oxidative stress, inflammation, and enhanced adhesion of monocytes to endothelial cells on the vessel wall. Febuxostat is a novel antigout agent recently reported to exert protective effects on endothelial dysfunction. This study aims to investigate the protective capacity of febuxostat against oxidized low-density lipoprotein (ox-LDL)-induced injury and monocyte attachment to endothelial cells. Human aortic valve endothelial cells (HAVECs) were stimulated with ox-LDL in the presence or absence of febuxostat (5 and 10 μM) for 6 hours. Mitochondrial reactive oxygen species were measured using MitoSox red staining, and the level of protein carbonyl was detected using enzyme-linked immunosorbent assay (ELISA). The expressions of IL-6, TNF-α, tissue factor (TF), VCAM-1, and ICAM-1 were evaluated with qRT-PCR assay and ELISA. Calcein-AM staining was used to determine the attachment of U937 monocytes to HAVECs. quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) and Western blot were used to measure the expression level of early growth response 1 (Egr-1) in HAVECs. First, the elevated expression of LOX-1, activated oxidative stress, excessive secreted inflammatory factors, and promoted expression of TF induced by stimulation with ox-LDL were significantly reversed by febuxostat, indicating a protective effect of febuxostat against endothelial dysfunction. Second, the upregulated VCAM-1 and ICAM-1, as well as the increased proportion of adhered monocytes to HAVECs induced by ox-LDL, were significantly alleviated by febuxostat. Finally, the promoted expression level of Egr-1 induced by ox-LDL was pronouncedly suppressed by febuxostat. We conclude that febuxostat protected HAVECs from ox-LDL–induced injury and monocyte attachment.